Optimization of Modern Technology in the Cultural Tradition of Butabuh Muli Mekhanai Luwah Lawang in Maghga Putih - Nuryamin, Nuryamin; Sinaga, Risma Margaretha; Adha, Muhammad Mona; Pargito, Pargito; Istiawati, Novia Fitria (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
The personality that has been attached to a region cannot be separated from the habits formed from the environment and culture that will gradually form a cultural identity. A region must have an identity and personality to maintain its existing characteristics, which can maintain its identity from the influence of other cultures. The presence of information and communication technology, especially smartphones, has an impact on muli meghanai to actively participate in the development of butabuh cultural traditions, this study aims to provide socialization from the globalization of the use of technological media as a means of butabuh cultural traditions to be preserved among adolescents. This scientific article was prepared using the Systematic Literature Review (SLR) method. The results showed that the use of technological media contributed to the butabuh cultural tradition. The use of technological media is claimed to be used as a tool to optimize butabuh culture in the national and international arena.